1980
DOI: 10.1073/pnas.77.4.1823
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of ilvGEDA operon attenuator region of Escherichia coli.

Abstract: The nucleotide sequence of the DNA thought to contain the control region for the ilvGEDA operon in Escherichia coli has been determined by the Maxam-Gilbert procedure. The sequence includes a region that, upon transcription, would yield a leader transcript specifying a peptide 32 residues long. This putative peptide would contain four leucine, five isoleucine, and six valine residues. A model is proposed that correlates the multivalent control of the ilvGEDA operon with the extent to which this leader transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
68
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 19 publications
4
68
0
Order By: Relevance
“…No regulatory protein has been identified that modulates expression of the operon in response to changes in the availability of the three amino acids. A leader-attenuator precedes the structural genes, and the proposed leader peptide includes residues of all three amino acids, consistent with the multivalent regulation of the operon (2,25,26,35). The data accumulated for the response of this operon to amino acid limitation are consistent with its being mediated via the leader-attenuator (26).…”
supporting
confidence: 64%
“…No regulatory protein has been identified that modulates expression of the operon in response to changes in the availability of the three amino acids. A leader-attenuator precedes the structural genes, and the proposed leader peptide includes residues of all three amino acids, consistent with the multivalent regulation of the operon (2,25,26,35). The data accumulated for the response of this operon to amino acid limitation are consistent with its being mediated via the leader-attenuator (26).…”
supporting
confidence: 64%
“…This ilv-specific regulation appears to be exclusively a consequence of an attenuation mechanism ( Fig. 1) (4,32,38). In principle, the attenuation mechanism controlling the ilv operon appears to be quite similar to that found to control operons involved in tryptophan (35), leucine (19), phenylalanine (61), histidine (3), and threonine (17) biosynthesis: the leader region specifies a short peptide containing a disproportionate frequency of the amino acids that are found to regulate the operon.…”
mentioning
confidence: 99%
“…Many of the amino acid biosynthetic operons of bacteria are regulated by attenuation. Each of these operons has a transcribed leader region containing a short peptide-encoding segment rich in codons for the regulatory amino acid(s) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). The presumptive leader peptides specified by these coding regions have been sought but have eluded detection.…”
mentioning
confidence: 99%